Scour depth under pipelines placed on weakly cohesive soils. (August 2015) - Postacchini, Matteo; Brocchini, Maurizio
Abstract : Highlights: Study of the scouring process around submarine pipelines placed on weakly cohesive seabeds. Analysis of laboratory tests. Direct dependence of the scour depth on the Keulegan–Carpenter parameter. Inverse dependence of the scour depth on the clay content for reduced amounts of clay. Formulations also derived for partially buried pipelines. Abstract: We here study the scouring processes that evolve around a submarine pipeline placed on a weakly cohesive seabed. We first analyze some laboratory tests carried out by Vijaya Kumar et al.[21], Xu et al.[25] and Zhou et al.[28] that focused on the scouring around a horizontal cylinder lying on a cohesive bed, subject to waves and currents. The specific purpose is that of finding a new formula for the prediction of the equilibrium scour depth under submarine pipelines. After a theoretical analysis of the main parameters, the sought formula has been found to be a function of: (i) the hydrodynamic forces acting on the cylinder (through the Keulegan–Carpenter parameter KC ), (ii) the clay content of the soil C c, and (iii) the burial depth e 0 / D . In the presence of small amounts of clay ( C c < 5 %), the scour depth depends directly on KC (as confirmed by many literature works for pipelines lying on sandy soils, e.g.[18] ) and inversely on C c (as already seen for bridge abutments on cohesive soils, e.g.[1] ), the best-fit law being characterized by a coefficient of determination R 2  = 0.62. If some burial depth is accounted for, this being a novelty of the present work, a more general formulation can be used, valid in the presence of weakly-cohesive soils and with burial depths of the pipe smaller than 0.5 ( R 2  = 0.79). For large clay-content ranges (2% <  C c  < 75 %), the scour depth depends directly on both KC and C c, this giving R 2  = 0.79 (no burial depth) and 0.91 (some burial depth). However, this finding is at odds with the main literature, because, for large amounts of clay, it is fundamental to consider the liquidity index LI, which accounts for some important clay properties, like the plasticity. We argue that the absence of LI is balanced by the direct dependence of the scour depth on C c . Notwithstanding the small number of available data, a formula for the prediction of the scour depth under pipelines lying on cohesive soils is fundamental for several engineering applications. The present contribution represents the first attempt to build such a formula, when the pipeline is subject to the wave-current forcing and the seabed is characterized by a relatively small clay content.